2020
DOI: 10.1155/2020/9048971
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Effect of Lactobacillus plantarum YS4 on Oxazolone‐Induced Colitis in BALB/c Mice

Abstract: In the present research, the effects of Lactobacillus plantarum YS4 (LP-YS4) on colitis were tested in an oxazolone-induced mouse model. BALB/c mice were induced by oxazolone and then treated with LP-YS4. The serum levels of mice were analyzed using commercial kits and the protein and mRNA expression levels of mouse colon tissue were detected by Western blotting and qPCR assay, respectively. The results demonstrated that LP-YS4 significantly (P<0.05) increased the colon length and ratio of colon weight/leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The mechanisms of inflammation involve the imbalance of the Th1/Th2 network system. Th1 and Th2 cells secrete IL‐2 and IL‐10 cytokines, respectively, which are directly associated with the development and progression of UC (Fiocchi, 2004; Yi et al., 2020). Low content of IL‐2 and a high content of IL‐10 indicate that the extent of UC is intensified (Song et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of inflammation involve the imbalance of the Th1/Th2 network system. Th1 and Th2 cells secrete IL‐2 and IL‐10 cytokines, respectively, which are directly associated with the development and progression of UC (Fiocchi, 2004; Yi et al., 2020). Low content of IL‐2 and a high content of IL‐10 indicate that the extent of UC is intensified (Song et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the mechanism responsible for producing the scratching in mice after repeated application with oxazolone resembles that of the itching in patients with AD ( 12 ). Oxazolone is also used to induce colitis and respiratory allergy ( 13 , 14 ). DNFB is an decoupling agent, first used to induce typical skin sensitization of the contact type in guinea pigs ( 15 ).…”
Section: Introductionmentioning
confidence: 99%